Metabolic syndrome and the risk of urothelial carcinoma of the bladder: a case-control study - Montella, Maurizio (BMC Cancer, 2015)
BACKGROUND: The Metabolic syndrome (MetS) is an emerging condition worldwide, consistently associated with an increased risk of several cancers. Some information exists on urothelial carcinoma of the bladder (UCB) and MetS. This study aims at further evaluating the association between the MetS and UCB. METHODS: Between 2003 and 2014 in Italy, we conducted a hospital-based case-control study, enrolling 690 incident UCB patients and 665 cancer-free matched patients. The MetS was defined as the presence of at least three of the four selected indicators: abdominal obesity, hypercholesterolemia, hypertension, and diabetes. Odds ratios (ORs) and corresponding 95 % confidence intervals (CIs) for MetS and its components were estimated through multiple logistic regression models, adjusting for potential confounders. RESULTS: Patients with MetS were at a 2-fold higher risk of UCB (95 % CI:1.38–3.19), compared to those without the MetS. In particular, ORs for bladder cancer were 2.20 (95 % CI:1.42–3.38) for diabetes, 0.88 (95 % CI: 0.66-1.17) for hypertension, 1.16 (95 % CI: 0.80-1.67) for hypercholesterolemia, and 1.63 (95 % CI:1.22–2.19) for abdominal obesity. No heterogeneity in risks emerged across strata of sex, age, education, geographical area, and smoking habits. Overall, 8.1 % (95 % CI: 3.9-12.4 %) of UCB cases were attributable to the MetS. CONCLUSIONS: This study supports a positive association between the MetS and bladder cancer risk.